右下顎角部に発生した筋線維腫症の1例 - 小川, 仁; 岡田, 益彦; 嶋﨑, 康相; 竹川, 政範; 藤盛, 真樹; 角, 伸博 (日本口腔外科学会雑誌, 2021)
We report a case of myofibromatosis involving the right mandibular angle in a 10-year-old child. Myofibromatosis is a rare benign tumor characterized by the proliferation of spindle-shaped myofibroblasts occurring in the skin, subcutaneous tissue, soft tissue, bone, and viscera. The tumor may present as a single nodule or multiple nodules. The patient was referred to our clinic with the chief complaint of swelling of the lower jaw. A panoramic radiograph showed a globe-like radiolucent lesion with an unclear margin in the right mandibular angle. T1-weighted magnetic resonance imaging (MRI) demonstrated low isointensity, T2-weighted MRI revealed high signal intensity at the site of the lesion, and contrast-enhanced MRI showed a marked contrast effect at the tumor margin. Biopsy results were consistent with a diagnosis of nodular fasciitis, usually associated with spontaneous regression. However, the lesion increased in size, and was thus surgically resected. The final diagnosis was myofibromatosis. Several reports suggest that myofibromatosis is difficult to distinguish from other lesions. The histopathological characteristics of the present case were similar to nodular fasciitis, and the diagnosis of the resected specimen was different from that at the time of biopsy. There was no evidence of recurrence in the 18 months after surgery.